Patterns of long-term opioid therapy with prior nonpharmacologic pain management utilization - McClure, David L.; Binswanger, Ingrid A.; Narwaney, Komal J.; Ford, Morgan A.; Nguyen, Anh P.; Rinehart, Deborah J.; Glanz, Jason M. (Scientific reports, 2025)
In 2022, the Centers for Disease Control and Prevention updated opioid prescribing guideline to emphasize use of non-addictive pharmacotherapies or nonpharmacologic procedures in place of or as an aid in starting the lowest feasible opioid dosage. However, the impact of nonpharmacologic pain management utilization on concurrent or subsequent opioid therapy dosing remains unexplored. We described patterns of nonpharmacologic pain management utilization prior to initial dose level in patients starting long-term opioid therapy. Utilizing electronic health data, we created a nonpharmacologic pain management utilization code list and applied it in a pre-existing cohort of patients with chronic pain prescribed long-term opioid therapy (LTOT) from August 2016 through September 2021. Univariate descriptions and bivariate associations of covariates with the initial LTOT mean daily morphine milligram equivalents (MME) categories were described via counts, percentages, and chi-square or Kruskal Wallis tests as appropriate. We also conducted a secondary multivariate regression analysis among patients with at least 12 months of health plan enrollment. There were 7679 patients for analysis with initial mean daily LTOT levels spanning 1 to 90 + MME. Nonpharmacologic therapies for pain management were infrequently utilized among patients starting LTOT and were dose dependent. This novel approach to identifying and categorizing nonpharmacologic therapies may help assess their clinical effectiveness in future studies.